The use of a thermographic camera in aiding the diagnosis of cellulite appearance - Ribeiro do Vale Silva, Julianna; Rodrigues de Araújo, Maria das Graças; Guerino, Marcelo Renato (O Mundo da Saúde, 2022)
Aesthetic cellulite is a disorder characterized by the skin with an “orange peel” appearance and has negatively affected the self-esteem and social life of more than 80% of post-pubertal women. The content in question covers the scarcity of evaluative studies in the area of aesthetics and favors the standardization of a technique for evaluating this dysfunction. The present study aimed to verify the use of thermography as an auxiliary method in the diagnosis of possible circulatory alterations in the gluteal region, as in cases of cellulite appearance, and to investigate the possibility of preventing its worsening. This is an observational study, carried out with eighteen female volunteers aged between 18 and 35 years old, with striae alba in the gluteal region, without drug treatment with photosensitive substances, or using isotretinoin, or still applying any specific topical treatment on the buttocks. The participants were divided into 2 groups, which were group 1 (non-uniform thermographic images) and group 2 (uniform thermographic images). Assessments of the cellulite’s appearance were performed through conventional photographs, thermography, and by 3 specialists in the field of dermatofunctional physiotherapy. The results showed that the severity of cellulite cannot be classified only through a visual assessment or questionnaires, since the participants who do not have the physical characteristic of cellulite, demonstrated through the thermography, a circulatory compromise, which suggests a possible risk in developing cellulite. Therefore, this study concluded that a previous diagnosis through a thermographic camera can help in the prevention of this dysfunction.